The role of savings in the economic development of the Republic of Azerbaijan - Nagi Bairamli; Vassilis Kostoglou (International Journal of Economic Sciences and Applied Research, 2010)
This article aims to analyze the possibilities of the accumulation and mobilization of savings and their role in the economic development of the Republic of Azerbaijan. Currently, the national economic growth is mostly based on the resource components; crude oil, natural gas and oil products. For the development of the non-oil sector the mobilization of domestic savings into investments would prove very useful. Savings of people should be the most important investment resource for the development of the non-oil sector, as the foreign capital is mostly involved in production of natural resources like oil and gas. The mobilization of domestic savings is crucial for raising the economic growth and promoting development, as it is the private savings that affect the domestic investments significantly. The most of the savings are made when they are fully channeled into the productive investments. As a result, this will lead to the solution of problems of employment and economic growth.
Keywords: O16; O11; E44; 330; economic growth and development; savings; investments; financial institutions